Pakaian Liturgis Sebagai Sarana Berteologi Dalam Pengalaman GPIB - John C Simon (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2022)
Abstract: This paper aims to clarify the polemics surrounding the implementation of the ordination of prospective pastors at GPIB, as well as to determine a clear and responsible theological position. The polemic was triggered by differences in the process of carrying out the ordination of prospective pastors in a congregation that was not in accordance with the usual practice which was the result of the decision of the synodal assembly. By using qualitative methods, literature and interviews, this paper intends to construct the meaning of a priest's ordination through the symbolization of the use of liturgical clothing or a white toga during the ordination worship procession. The results of this study found that the meaning of pastoral ordination is in the tradition of baptism in the early church, reformatory theology about the priesthood of believers, and synodal decisions about pastoral ordination. His form is a prospective pastor who will be ordained already wearing liturgical clothes or a white toga since the procession into the church building. Imposition means that a person is fit to wear the symbol of liturgical clothing to be a servant of God in His holy house and in other pastoral duties.Â Keywords: liturgical clothing, theology, GPIBÂ Abstrak: Tulisan ini bertujuan memperjelas polemik di seputar pelaksanaan penahbisan calon pendeta di GPIB, sekaligus menentukan posisi teologis yang jelas dan bertanggungjawab. Polemik tersebut dipicu oleh perbedaan dalam proses pelaksanaan penahbisan calon pendeta di sebuah jemaat yang tidak sesuai dengan kebiasaan yang lazim yang merupakan hasil keputusan sidang sinodal. Dengan menggunakan metode kualitatif, kepustakaan dan wawancara, tulisan ini bermaksud mengonstruksi makna penahbisan pendeta melalui simbolisasi penggunaan pakaian liturgis atau toga putih pada saat prosesi ibadah penahbisan tersebut. Hasil penelitian ini menemukan bahwa makna tahbisan pendeta terdapat dalam tradisi baptisan di gereja perdana, teologi reformatoris tentang imamat am orang percaya, dan keputusan secara sinodal tentang penahbisan pendeta. Wujudnya adalah seorang calon pendeta yang akan ditahbiskan sudah mengenakan pakaian liturgis atau toga putih sejak prosesi masuk gedung gereja. Pengenaan itu bermakna bahwa seseorang dilayakkan mengenakan simbol pakaian liturgis untuk menjadi seorang pelayan Allah di dalam rumah-Nya yang kudus dan di dalam tugas-tugas kegembalaan lainnya.Kata kunci: pakaian liturgis, teologi, GPIB